Negative word of mouth (NWOM) using compartmental epidemiological models in banking digital transformation - Mariano Méndez Suárez; Ignacio Danvila del Valle; Cristina Blanco González-Tejero; Sorin Gavrila Gavrila (Contemporary Economics, 2023)
Our article is among the first to model the reactions of customers to the digital transformation of European banks in a scenario of declining interest margins. Motivated by the hypothesis that customers' feelings, perceptions and negative reactions towards digital transformation are channeled through the spread of negative word-of-mouth (NWOM) in a way analogous to the spread of a disease epidemic, we propose and analyze a compartmentalized mathematical model using data from a medium-sized Spanish commercial bank. To understand the NWOM phenomenon with an epidemiological approach we consider some realistic interactions in a social network and we formulate a novel application of the susceptible-exposed-infected-recovered-mortality (SEIRM) model. The results indicate that a better understanding of consumers' negative reactions and their correct monitoring can help banks improve profitability when facing a digital transformation process. In summary, the research warns commercial bank managers about the need to carefully assess the effects of changes brought about by digital transformation and the development fee management strategies based on the behavior of customer groups, as well as the deployment of new churn risk management methods to deal with the most disengaged customers.
Keywords: L22; M30; 330; NWOM; negative word of mouth; epidemiological models; banking; digital transformation